Lateral-torsional stability for curved 6061-T6 structural aluminium alloys - Tebo, E-P. T. (Vaal University of Technology, 2020)
Though aluminium (Al) is justifiably described as a green metal with an increasing rate of application in structures, designers still restrain themselves from its applications as a load-bearing skeleton in structure due to insufficient design guidelines. This insufficient information is more with channel sections that might experience lateral-torsional buckling (LTB) when used as a load-bearing skeleton in structures. This study investigates the effects on imperfections on LTB load-carrying stability for 6061-T6 Al alloy channel section arches and proposed design guidelines. The case study focused on freestanding circular fixed end arches subjected to a transverse point load at the shear centre. The software package Abaqus was used to study a total of 110 arch models from three separate channel sections with an additional 16 arch models for validation. Sixty-six channel arches were developed at a constant length, while the remaining 44 arches were formed at constant slender ratios using 11 discrete included angles. The FE analyses methods used for the investigation were validated with existing analytical methods and showed good agreement, despite the assumptions of the bilinear curve used for material nonlinearity, initial geometric imperfections and residual stresses that presented the imperfections of the models. The different investigated factors include slender ratios, change in cross-section area, imperfections, and angles. These factors were found to have substantial impacts on the prebuckling state, which turns to impact LTB behaviour and load-carrying capacity. From arches developed at constant span length, the arches with moderately included angles (50°≤2𝛼≤90°) were found suitable for the designs against LTB, followed by the shallow (2𝛼<50°) and deep arches (90°<2𝛼≤180°) respectively. For arches developed at constant slender ratios, the deep arches were found to be more suitable in the design against LTB, followed by the moderate and shallow arches, respectively. In addition, it was realised that the change in web-flange thickness, section depth and slender ratios, had significant effects on the LTB loads magnitudes and very insignificant effects on the general behaviour across the included angles. The same occurrence was also observed on the prebuckling analyses. All the investigated channel section arches showed the imperfections to have significant impacts on the LTB loads. Arches developed at constant span length showed the maximum elastic LTB loads to have overestimated the expected real LTB loads by approximately 48 percent. While the maximum elastic LTB loads of arches developed at 𝑆𝑟𝑥⁄= 60 and 90 showed that the real LTB loads were overestimated by about 39 and 14 percent, respectively. That said, the elastic LTB loads on average overestimated the real LTB loads by over 50 percent for the arches developed at the constant span length and by only 18 percent for arches developed at the constant slender ratios.
M. Tech. (Department of Mechanical Engineering, Faculty of Engineering and Technology), Vaal University of Technology.
Keywords: Lateral-torsional buckling; Aluminium alloys; Prebuckling; Dissertations, Academic -- South Africa.; Buckling (Mechanics).; Elasticity.; Aluminum alloys.; Aluminum, Structural.